MANAJEMEN PENANGANAN INFEKSI PARASIT PADA PASIEN KELINCI DI KLINIK HEWAN JOGJA PERIODE 23 JUNI 2013 - 15 MARET 2014 - , ENDAH PURWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Parasite infestation is one of the cause harmful disease that occurs in rabbits. The purpose of this work is to investigate the diseases of rabbits caused by parasitic infections and how to handle the rabbits in Klinik Hewan Jogja. Data were collected by recording the data of rabbit ambulatoir cards period of 23 June 2013 - 15 March 2014. Parasitic infestation in rabbits in Klinik Hewan Jogja were scabies, coccidiosis and fleas. Symptoms of scabies of the rabbits revealed thin, limp, hair loss in the part of body and scratched the itchy area. Symptoms of coccidiosis in rabbits were limp, pale mucous and the laboratory examination were positive for coccidiosis. Symptoms of lice infested rabbit were scratching the itchy , hair loss and the lice has found in their hairs. Treatment for scabies infestations in Klinik Hewan Jogja were grooming by using shampoo for thick and mites and then were injected with ivermectin. Coccidiosis infestation were treated with NaCl, Enzyplex and also ivermectin. Fleas infestation in Klinik Hewan Jogja were handled by grooming regularly.